Effect of Inflation, Exchange Rates, and Interest Rates on Financial Sector Share Prices - Ita Sitasari; Yoga Firmansyah (International Economic and Finance Review, 2022)
The financial sector share price has a high performance on the Indonesia Stock Exchange during 2010-2020. This condition indicates that investors have an interest in companies in the financial sector. This research aims to find out the effect of inflation, exchange rates, and interest rates on the stock prices of the financial sector. The study uses a quantitative approach, research data used during the years 2010-2020. Processing data uses reviews applications that first use classic assumption tests and multiple regressions. The research showed that simultaneously inflation, interest rates, and exchange rates affect stock prices, while partially showed that exchange rates have a positive effect on stock prices, interest rates negatively affect stock prices, while inflation does not affect stock prices. This research model shows an effect on the stock price by 78%.